SISTEM REKOMENDASI PEMILIHAN MOBIL MENGGUNAKAN METODE MOORA - Galuh Pradana; Rara Sri Artati Rejeki (Elkom: Jurnal Elektronika dan Komputer, 2023)
Many manufacturers create numerous types of automobiles with diverse advantages ranging from engine capacity, type of design, and fantastic features to their products in response to the large number of enthusiasts and requests from the general public. Consumers are frequently perplexed while making decisions regarding brand, model, type, price, engine capacity, transmission, year of manufacturing, fuel capacity, and other aspects of the car's benefits due to the growing range of options available. Brand, model, type, price, engine and transmission size, year of production, and gasoline capacity are all factors in choosing a car. The MOORA system only recommends vehicles from the three well-known manufacturers Honda, Toyota, and Suzuki. A Honda CRV with a value of Y_i = 0.225 was recommended as the first recommendation, followed by a Honda BRV with a value of Y_i = 0.211, and a Honda Brio with a value of Y_i = 0.204. The recommendations were based on Honda brand criteria and CVT transmission.